Strategi Pembelajaran Al Qur'an Berbasis Metode Ummi untuk Pembinaan Orang Dewasa di Majelis Taklim - Della Pramudita; Astuti Darmiyanti; Fatimah Az Zahro (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The ability to recite the Qur'an accurately and in accordance with the rules of tajwid is an essential competency for every Muslim. Therefore, appropriate learning strategies are needed to accommodate learners' characteristics and improve the effectiveness of Qur'anic instruction. One of the widely implemented approaches is the Ummi Method, which emphasizes gradual, systematic, and practice-oriented learning. This study aims to describe the learning strategies based on the Ummi Method at Majelis Qur'an Ummahat Karawang. A descriptive qualitative approach was employed. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. Data credibility was ensured through source and technique triangulation. The findings reveal that the learning strategy begins with systematic planning, including the formulation of learning objectives, identification of learners' initial abilities, determination of learning targets, and preparation of instructional media based on the Ummi Method standards. The implementation stage applies the mother language approach, direct method, repetition, read-and-listen activities, and instructional teaching aids. These strategies contribute to a more structured learning process, encourage learner participation, and improve Qur'anic reading accuracy, learning motivation, and self-confidence.